Productivity analysis by using firm-level data: The case of Macedonia - Biljana Jovanovic (National Bank of the Republic of Macedonia, 2018)
Productivity, the efficiency by which firms convert inputs into output is central concept in growth related discussions. This research is focused on analyzing productivity on a sample of Macedonian firms. The goal is twofold - first, to construct productivity indicators by using firm-level data, with special focus to construction of total factor productivity (TFP), and, second to identify productivity determinants specific for Macedonian firms. Results are in line with the global productivity trends - there is significant slowdown in productivity growth in 2016. This is true for labour productivity, as well as for the TFP measure. However, the period is relatively short to conclude that this shift is of permanent, structural nature, especially having in mind the trend of reducing unemployment in the economy. As productivity determinants are concerned, econometric research confirms the importance of financial health, human capital and firms' size as significant factors that affect the productivity of Macedonian firms.
Keywords: D22; D24; 330; micro data; productivity; total factor productivity